Psychological Well-Being: Collective Identity and Discrimination in Stigmatized Neighborhoods - García, Felipe E.; Castillo, Bernarda; García, Angelina; Smith Castro, Vanessa (Pensando Psicología, 2017)
Introduction: Social discrimination and stigmatization of individuals for belonging to a particular group, specifically for their place of residence in this case, is a major problem and affects well-being and mental health. Purpose: The objective of this study was to establish the relative influence of collective identity and the perception of discrimination on the psychological well-being of inhabitants of stigmatized neighborhoods. Method: The sample consisted of 160 adults (50% women) living in stigmatized neighborhoods in the province of Concepción, Chile. The instruments used were Keyes’s Mental Health Continuum-Short Form (MHC-SF) for the measurement of psychological well-being, the Van Zomeren’s Collective Identity Scale and the Discrimination Experiences Scale adapted to the Latin American context by Smith-Castro. Results: The results show psychological well-being is negatively influenced by discrimination and positively influenced by collective identity. Conclusions: Strengthening the sense of belonging and endogroup pride could enable environments and living conditions that promote mental health and healthy lifestyles.